2009
DOI: 10.1111/j.1750-3639.2008.00256.x
|View full text |Cite
|
Sign up to set email alerts
|

Modified C‐Reactive Protein Is Expressed by Stroke Neovessels and Is a Potent Activator of Angiogenesis In Vitro

Abstract: Native C-reactive protein (nCRP) is a pentameric oligo-protein and an acute phase reactant whose serum expression is increased in patients with inflammatory disease. We have identified by immunohistochemistry, significant expression of a tissue-binding insoluble modified version or monomeric form of CRP (mCRP) associated with angiogenic microvessels in peri-infarcted regions of patients studied with acute ischaemic stroke. mCRP, but not nCRP was expressed in the cytoplasm and nucleus of damaged neurons. mCRP c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(97 citation statements)
references
References 46 publications
5
90
0
2
Order By: Relevance
“…This has led us to propose that the dissociation of the CRP molecule is an activating mechanism that is required for the expression of enhanced bioactivities and is also a buffering mechanism that localizes the actions of mCRP into inflammatory loci to prevent the possible global effects directly induced by large-scale alterations in the serum levels of CRP [73]. Consistent with our proposal, immunohistochemical analyses using highly specific antibodies revealed that mCRP, not CRP, was the major isoform present in local lesions, including atherosclerotic plaques [55,76], diabetic kidneys [77] and stroke neovessels [78].…”
Section: Dissociation Of Crp Localizes the Enhanced Bioactivitiessupporting
confidence: 71%
“…This has led us to propose that the dissociation of the CRP molecule is an activating mechanism that is required for the expression of enhanced bioactivities and is also a buffering mechanism that localizes the actions of mCRP into inflammatory loci to prevent the possible global effects directly induced by large-scale alterations in the serum levels of CRP [73]. Consistent with our proposal, immunohistochemical analyses using highly specific antibodies revealed that mCRP, not CRP, was the major isoform present in local lesions, including atherosclerotic plaques [55,76], diabetic kidneys [77] and stroke neovessels [78].…”
Section: Dissociation Of Crp Localizes the Enhanced Bioactivitiessupporting
confidence: 71%
“…Studies from our group and others have also demonstrated that CRP and PTX3 distribution within the atherosclerotic lesions distinctly differs [11,32]. For instance: 1) PTX3 and not CRP is augmented in complicated plaques compared to fibroatheroma whereas CRP but not PTX3 is more accumulated in fibroatheroma than in atheroma; 2) PTX3 is found to be quite sparse in lipid-rich regions of the fibroatheroma lesions whereas CRP is found to be particularly intense surrounding and within the lipid core; 3) PTX3 and CRP colocalize with macrophages but PTX3 and not CRP correlates with the extent of M2 macrophage phenotype (presents anti-inflammatory properties); and, 4) although PTX3 is notably abundant in areas of intraplaque hemorrhage where CRP is scarce, CRP has been strongly detected around areas of newly formed microvessels suggesting CRP contribution to neovascularization [11,33,34]. Overall, these observations suggest that CRP and PTX3 may play distinct biological roles in atherosclerosis and ensuing thrombotic complications.…”
Section: Pentraxins In Atherosclerosismentioning
confidence: 96%
“…However, it must be taken into consideration that the therapeutic inhibition of mCRP generation might reduce the proangiogenic effect of mCRP that has been described recently. 34 Inflammation as such is not necessarily harmful, but uncontrolled inflammation may be detrimental in conditions such as ischemia/ reperfusion injury. Similarly, the proangiogenic effects of mCRP may be beneficial; however, in the context of an exaggerated inflammatory response, they may have less relevance.…”
Section: Discussionmentioning
confidence: 99%